Co-creation and co-operation in business models - Mirowski, Mateusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The value co-creation, as a method of creating value in relations between enterprises and customers, is a reality that brings benefits for both sides. Practical business solutions presented in the article force to ask a question about topicality of the assumption that only the company is able to create a value to be exchanged on the market. Perhaps the best opinion that sums up this paper was brought by Harvard University mathematical biologist Martin Nowak in his article Five rules for the evolution of cooperation published in the Science Magazine: The two fundamental principles of evolution are mutation and natural selection. But evolution is constructive because of cooperation. New levels of organization evolve when the competing units on the lower level begin to cooperate. Cooperation allows specialization and thereby promotes biological diversity. Cooperation is the secret behind the open endedness of the evolutionary process. Perhaps the most remarkable aspect of evolution is its ability to generate cooperation in a competitive world. Thus, we might add ‘natural cooperation’ as a third fundamental principle of evolution beside mutation and natural selection.
Keywords: współtworzenie wartości; współpraca przedsiębiorstw; marketing; sieciowość; zorientowanie na klienta